A Breathable and Screen‐Printed Pressure Sensor Based on Nanofiber Membranes for Electronic Skins. Issue 2 (4th December 2017) - Yang, Wei; Li, Nian‐Wu; Zhao, Shuyu; Yuan, Zuqing; Wang, Jiaona; Du, Xinyu; Wang, Bin; Cao, Ran; Li, Xiuyan; Xu, Weihua; Wang, Zhong Lin; Li, Congju
Abstract: In recent years, skin‐like pressure sensors with high sensitivity and excellent flexibility are widely demonstrated for electronic skins. However, most of the reported skin‐like pressure sensors are still based on airtight films, resulting in limited air permeability. Herein, cost‐effective and capable processes of large‐scale production are reported for lightweight and breathable pressure sensors based on nanofiber membranes (NM). The pressure sensor is composed of a layer‐by‐layer structure of poly(vinylidene fluoride) NM for substrates, silver nanowires for electrodes, and thermoplastic polyurethane NM for the dielectric layer through screen printing and ultrasonic bonding techniques. Benefiting from the high porosity of NM, the capacitive pressure sensor possesses unique performance, including a superior sensitivity of 4.2 kPa −1, a fast response time (<26 ms), an ultralow detection limit (1.6 Pa), and excellent breathability (Gurley value = 17.3 s/100 mL). Furthermore, the pressure sensor is not only applicable to monitor human physiological signals, but also to detect spatial pressure distribution. These results indicate that the breathable and screen‐print pressure sensor is promising for electronic skins with air permeability. Abstract : To improve air permeability of skin‐like pressure sensors for electronic skins, nanofiber membranes for substrates and dielectric layer are used to fabricate a breathable and screen‐printed capacitive pressure sensor. Based on porous membranes, the pressure sensor exhibits high sensitivity, fast response speed, and excellent air permeability, providing a new approach for electronic skins.